Identification of a pentatricopeptide repeat RNA editing factor in Physcomitrella patens chloroplasts. Issue 21 (30th September 2014) - Ichinose, Mizuho; Uchida, Masato; Sugita, Mamoru
Abstract : The moss Physcomitrella patens has two RNA editing sites in the chloroplasts. Here we identified a novel DYW‐subclass pentatricopeptide repeat (PPR) protein, PpPPR_45, as a chloroplast RNA editing factor in P . patens . Knockdown of the PpPPR_45 gene reduced the extent of RNA editing at the chloroplast rps14 ‐C2 site, whereas over‐expression of PpPPR_45 increased the levels of RNA editing at both the rps14 ‐C2 site and its neighboring C site. This indicates that the expression level of PpPPR_45 affects the extent of RNA editing at the two neighboring sites. Abstract : DYW‐subclass pentatricopeptide repeat protein PpPPR_45 is localized in chloroplasts. PpPPR_45 is an RNA editing factor in chloroplasts. PpPPR_45 is involved in RNA editing at two adjacent sites of rps14 transcript.